Assessment of heavy metal contamination and sediment characteristics in Ozomu lake, southern Nigeria: Implications for environmental health - John O. Olomukoro; Clinton O. Enabulele (Kuwait Journal of Science)
This study investigates heavy metal concentrations and surface sediment characteristics in the Ozomu Lake, located in southern region of Nigeria. Sediment samples were systematically collected across three stations, over six months, spanning from March to August. This period encompasses the transition from the late dry season to the early wet season, offering valuable insights into the seasonal variations of heavy metal distribution and sediment properties. The concentrations of heavy metals in the sediment were determined using standard methods, along with the analysis of particle size distribution and organic content (% organic carbon and % organic matter). Essential findings reveal significant values. Iron (Fe) averaged 1194.86 mg/kg, zinc (Zn) 30.71 mg/kg, copper (Cu) 14.80 mg/kg, manganese (Mn) 17.43 mg/kg, lead (Pb) 1.17 mg/kg, and cadmium (Cd) 0.18 mg/kg. Enrichment factor (EF) assessments indicate notable enrichment in Fe, Zn, Cu, Mn, and Cd. Key sediment properties include total organic carbon (%TOC) at 4.46%, total organic matter (%TOM) at 7.72%, and particle size distribution with clay at 8.99%, silt at 6.24%, and sand at 84.77%. Principal component analysis (PCA) uncovers intricate relationships among heavy metals, shedding light on their sources and distribution. Geo-accumulation indices (Igeo) reveal moderate pollution levels in Fe and Cd, suggesting potential ecological risks. Conversely, Zn, Cu, Mn, and Pb remain within unpolluted ranges. The study enhances our understanding of heavy metal contamination in Ozomu Lake, emphasizing the need for tailored management and conservation strategies. Future research should explore seasonal variations and specific pollution sources in the lake's catchment area. This study contributes valuable insights into Ozomu Lake's environmental dynamics and underscores the importance of sustainable management for its long-term health and ecological integrity.